(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2007)
The paper is a study based in the History of Brazil, and intends to investigate the evolution of the representative democracy in our country, as well as analyses the crisis of the political parties that, today, in the very Century XXI, do not go beyond mere acronyms, what was proved in the last elections of 2006. It is clear, then, that they do not support an ideology, but just interests of a minority, if not their own, in spite of the will of the coletivity. Concluding, it was included in this research the demonstration of a people in their contention about the collapse of the representative democracy, when we see now the society willing the nule vote, clearly contradicting the fiercely aimed popular vote, in the move called “Diretas-Já” [Directs Now].